A Randomized Clinical Trial Examining the Effect of Video‐Based Prevention of Alcohol and Marijuana Use Among Recent Sexual Assault Victims. (25th October 2017) - Walsh, Kate; Gilmore, Amanda K.; Frazier, Patricia; Ledray, Linda; Acierno, Ron; Ruggiero, Kenneth J.; Kilpatrick, Dean G.; Resnick, Heidi S.
Abstract : Background: This study examined whether a brief video intervention (Prevention of Post‐Rape Stress [PPRS]) delivered in the emergency department to recent sexual assault (SA) victims reduced alcohol and marijuana use at 3 points over the course of a 6‐month follow‐up compared to treatment as usual (TAU) and an active control condition (Pleasant Imagery and Relaxation Instruction [PIRI]). Prior assault history, minority status, and pre‐SA substance use also were examined as moderators of intervention efficacy. Methods: Women aged 15 and older ( N = 154) who participated in a post‐SA medical forensic examination were randomly assigned to watch the PPRS video ( n = 54) or the PIRI video ( n = 48) or receive TAU ( n = 52) and completed at least 1 follow‐up assessment targeted at 1.5 (T1), 3 (T2), or 6 (T3) months following the examination. Results: Regression analyses revealed that, relative to TAU, PPRS was associated with less frequent alcohol use at 6 months post‐SA among women reporting pre‐SA binge drinking and minority women. Relative to TAU, PPRS also was associated with fewer days of marijuana use at T1 among those who did not report pre‐SA marijuana use and prior SA. Findings for pre‐SA marijuana use were maintained at T3; however, findings for prior SA shifted such that PPRS was associated with fewer days of marijuana use at T3 for women with a prior SA. Conclusions: PPRS may be effective at reducing substance use for some recent SA victims, including those with a prior SA history, a prior substance use history, and minority women. Abstract : Recent rape victims who had a prior history of assault and received a brief video intervention, Prevention of Post‐Rape Stress (PPRS), reported fewer days of marijuana use at T3 (6.5 months after the index rape) compared to those with a prior history who received an active control, Pleasant Imagery and Relaxation Instruction (PIRI). Although the video did not confer benefit among those without a prior history, findings for the high‐risk group with a prior history are promising.